Optimized Sedation Improves Colonoscopy Quality Long-Term. (8th January 2015) - Triantafyllou, Konstantinos; Sioulas, Athanasios D.; Kalli, Theodora; Misailidis, Nikolaos; Polymeros, Dimitrios; Papanikolaou, Ioannis S.; Karamanolis, George; Ladas, Spiros D.
Abstract : Background . Quality monitoring and improvement is prerequisite for efficient colonoscopy. Aim . To assess the effects of increased sedation administration on colonoscopy performance. Materials and Methods . During Era 1 we prospectively measured four colonoscopy quality indicators: sedation administration, colonoscopy completion rate, adenoma detection rate, and early complications rate in three cohorts: cohort A: intention for total colonoscopy cases; cohort B: cohort A excluding bowel obstruction cases; cohort C: CRC screening-surveillance cases within cohort B. We identified deficiencies and implemented our plan to optimize sedation. We prospectively evaluated its effects in both short- (Era 2) and long-term period (Era 3). Results . We identified that sedation administration and colonoscopy completion rates were below recommended standards. After sedation optimization its use rate increased significantly (38.1% to 55.8% to 69.5%) and colonoscopy completion rate increased from 88.3% to 90.6% to 96.4% in cohort B and from 93.2% to 95.3% to 98.3% in cohort C, in Eras 1, 2, and 3, respectively. Adenoma detection rate increased in cohort C (25.9% to 30.6% to 35%) and early complications rate decreased from 3.4% to 1.9% to 0.3%. Most endoscopists increased significantly their completion rate and this was preserved long-term. Conclusion . Increased sedation administration results in long-lasting improvement of colonoscopy quality indicators.